2020
DOI: 10.3390/cli8120148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daily Precipitation from the ERA5 Global Reanalysis against GHCN Observations in the Northeastern United States

Abstract: Precipitation is a primary input for hydrologic, agricultural, and engineering models, so making accurate estimates of it across the landscape is critically important. While the distribution of in-situ measurements of precipitation can lead to challenges in spatial interpolation, gridded precipitation information is designed to produce a full coverage product. In this study, we compare daily precipitation accumulations from the ERA5 Global Reanalysis (hereafter ERA5) and the US Global Historical Climate Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Comparisons between ERA5 and GHCN measurements have been made in the past for precipitation in the Northeastern United States. This study found that distance from the coast and elevation affected the precipitation relationship between the two data sets [8]. These results suggest that differences between air temperature measurements will also be found between the data sets.…”
Section: Introductionmentioning
confidence: 60%
“…Comparisons between ERA5 and GHCN measurements have been made in the past for precipitation in the Northeastern United States. This study found that distance from the coast and elevation affected the precipitation relationship between the two data sets [8]. These results suggest that differences between air temperature measurements will also be found between the data sets.…”
Section: Introductionmentioning
confidence: 60%
“…The reduction (see the follow‐up discussion on Figure 3a1 for level of reduction) in both wet and dry bias of ERA5 rainfall as compared to ERA‐Interim over EA indicates the improvement of the model in handling the sensitivity to orography. The wet bias in ERA‐Interim is reduced in ERA5 as noted by different researches over different areas (Karypidou & Katragkou, 2018; Crossett et al ., 2020; Gleixner et al ., 2020; Hersbach et al ., 2020). Most parts of EA represent the region where the wet bias in ERA5 relative to each reference rainfall is significantly reduced in comparison to the wet bias in ERA‐Interim relative to the same reference rainfall particularly during SOND and DJF.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) and Crossett et al . (2020) over North America, Gleixner et al . (2020) and Karypidou & Katragkou (2018) over Africa, and Xu et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The wind profile data is used to estimate “near‐surface” wind components. Note that ERA5 resolves the mean orography at 0.25° scale, but also has sub‐grid scale orography to better represent the momentum transfers due to small‐scale variations in orography (ECMWF 2019; Crossett et al., 2020). This needs to be considered in the comparison of ERA 5 precipitation with the other products.…”
Section: Datamentioning
confidence: 99%